The Impact of Digital Marketing, Halal Labels, Product Quality, and Price on Consumer Satisfaction in the Halal Industry: A Study on Shopee and TikTok Shop - Muhammad Zaky Hermawansyah; Adi Mansah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the impact of digital marketing, halal labeling, product quality, and price on customer satisfaction in the halal industry sector, especially on e-commerce platforms such as Shopee and TikTok Shop. By utilizing the Theory of Planned Behavior (TPB) approach, this study explores the relationship between attitudes, subjective norms, and perceived behavioral control on consumer satisfaction in the context of halal products. The research uses quantitative methods with a causal research design. Data were collected through an online questionnaire using a 4-point Likert scale, involving 131 respondents selected via a purposive sampling technique. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The research findings indicate that price is the most influential factor on customer satisfaction, followed by product quality and digital marketing. Competitive prices and products that meet consumer expectations significantly increase satisfaction levels. In contrast, halal labeling does not have a significant direct influence on customer satisfaction, unless supported by other variables. This research contributes both in theory and practice in understanding Muslim consumer behavior in the digital era and can be a reference for industry players. designing effective and inclusive marketing strategies.